2004
DOI: 10.1080/00365590310025532
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous urothelial‐type adenocarcinoma of the prostate

Abstract: A case of mucinous urothelial-type adenocarcinoma of the prostate in a 68-year-old man is reported. This is a rare neoplasm which probably originates from the proximal prostatic ducts or the prostatic urethra. This tumor does not express prostate-specific antigen, in contrast to the more common mucinous adenocarcinoma of the prostate, and may be misdiagnosed as a secondary, mainly colorectal, tumor. Clinical examinations and immunohistochemistry may help in the differential diagnosis. Owing to local recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 1 publication
2
23
2
Order By: Relevance
“…5 Mucin-producing urothelial-type adenocarcinoma of the prostate is very rare and may arise from the prostatic urethra or prostatic ducts (in a background of urothelial metaplasia), possibly from urethritis glandularis or glandular metaplasia with malignant transformation and is analogous to adenocarcinoma arising from the urinary bladder and may also originate from periurethral structures such as Cowper (bulbourethral) or Littre glands. 54,136,137 Unlike conventional prostatic adenocarcinoma, cytokeratin 7 has been reported as strongly immunoreactive, consistent with an origin of the urothelium of the prostatic urethra or proximal prostatic ducts. 3A-D).…”
Section: Signet Ring Cell Differentiation and Primary Signet Ring Celmentioning
confidence: 88%
See 2 more Smart Citations
“…5 Mucin-producing urothelial-type adenocarcinoma of the prostate is very rare and may arise from the prostatic urethra or prostatic ducts (in a background of urothelial metaplasia), possibly from urethritis glandularis or glandular metaplasia with malignant transformation and is analogous to adenocarcinoma arising from the urinary bladder and may also originate from periurethral structures such as Cowper (bulbourethral) or Littre glands. 54,136,137 Unlike conventional prostatic adenocarcinoma, cytokeratin 7 has been reported as strongly immunoreactive, consistent with an origin of the urothelium of the prostatic urethra or proximal prostatic ducts. 3A-D).…”
Section: Signet Ring Cell Differentiation and Primary Signet Ring Celmentioning
confidence: 88%
“…30,133 Epstein et al 124 investigated 15 urinary bladder adenocarcinomas and 9 urinary bladder tumors with mixed glandular and transitional features and found that of the 11 urinary bladder adenocarcinomas in men, 3 were immunoreactive PSAP, and of the 5 urinary bladder tumors with mixed glandular and transitional features in men, 1 was immunoreactive for PSAP. 54,[136][137][138][139][140] Mucinous urothelial-type adenocarcinoma contains large pools of mucin lined by tall columnar cells with areas of mucin dissecting into the stroma forming pools and perhaps occasional signet ring cells, but unlike mucinous prostatic adenocarcinoma, they do not demonstrate tubules or cribriform glands floating within the mucin (Figs. 124 The colon and urinary bladder closely approximate the prostate, and a mucinous adenocarcinoma of either of these organs may invade the prostate by direct extension.…”
Section: Signet Ring Cell Differentiation and Primary Signet Ring Celmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Mucinous adenocarcinoma of the male urethra (MAU) is extremely rare, with only a handful of cases reported in the literature since 1961. [4][5][6][7][8][9][10][11][12][13][14] A recent study of primary urethral cancers in men and women found no association between histology and overall survival, 15 but other work focusing only on men reported better overall survival…”
Section: Introductionmentioning
confidence: 99%
“…Adenocarcinoma of prostate with mucinous differentiation arising in the male urethra is extremely rare. To our knowledge, only 21 cases were reported in the previous literature [ 1 5 ]. Here we report a case of unsuspected urothelial-type adenocarcinoma of the prostate in a patient with inverted papilloma of the bladder.…”
Section: Introductionmentioning
confidence: 99%